RETRACTED: Environmental and resource components in the development of subregions of the tourist territory - Shashkova Nina; Lukyanova Yelena; Shulga Marina; Kazak Anatoliy; Bukreev Igor; Fastunova Victoria (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001